Customer-Centric Technology: A Science Mapping of Marketing Transformation - Zulfikar, Rizka; Suryadi, Nanang; Valen Prasarry, Yudhita (Management Institute Faculty of Economics Universitas Andalas, 2025)
This research aimed to analyze the impact of technology on marketing practices, from the adoption stage to the creation of customer experience, through a bibliometric approach. Using 133 articles published between 2000 and 2024 obtained from Scopus.com database, the study compiled a comprehensive literature analysis to identify key trends, dominant research themes, and gaps in the literature. The article selection process was carried out using the PRISMA method with keywords such as